Trucks, triangles and a quiet life: Welfare implications of the European trucks cartel - Christian Beyer; Elke Kottmann; Korbinian von Blanckenburg (Philipps-University Marburg, School of Business and Economics, 2018)
We present a pragmatic approach to calculating the total economic loss induced by a cartel, focusing on the European trucks cartel (1997-2011). Overall, we estimate a net welfare loss of approximately exteuro0.7 bn. and an overcharge below 1% ( exteuro1.8 bn.). The cartel overcharge is surprisingly low. We explain this by (1) the existence of a reference market with an already elevated price level and (2) by other industry-specific factors that encourage cartel arrangements. In the case of the trucks cartel, the companies involved have apparently preferred the Hicksian "quiet life" of the monopolist to a further maximization of profits.
Keywords: D43; D61; L62; 330; Cartel; Welfare; Efficiency; Overcharge; Trucks